Effect of packaging and storage time on survival of Listeria monocytogenes on shelf-stable meat snacks - Uppal, Kamaldeep Kaur (Kansas State University, 2010)
The United States Department of Agriculture’s Food Safety and Inspection Service require that processors of ready-to-eat (RTE) meat and poultry products implement post- processing intervention strategies for controlling Listeria monocytogenes. The objective of our study was to determine the effect of packaging methods and storage time on reducing L. monocytogenes in shelf-stable meat snacks. Commercially available kippered beef steak strips (14 × 2.5 cm rectangle piece) and turkey tenders (4 × 4 cm square piece) were dipped into a five-strain L. monocytogenes cocktail, and dried at 23°C until a water activity of approximately 0.80 was achieved. Inoculated samples were packaged with four treatments: 1) vacuum, 2) nitrogen flushed with oxygen scavenger, 3) heat sealed with oxygen scavenger, and 4) heat sealed without oxygen scavenger. Samples were stored at 23°C and evaluated for L. monocytogenes levels at 0, 24, 48, and 72 h. Initial levels (time 0) of L. monocytogenes were approximately 5.7 log CFU/cm[superscript]2 for steak and tenders. For kippered beef steak, there was no interaction among packaging treatments and storage times (P > 0.05) whereas, storage time was different (P <0.05). A 1 log reduction of L. monocytogenes was observed at 24 and 48 h at 23°C for all packaging treatments and a 2.1 log CFU/cm[superscript]2 reduction occurred at 72 h. A 1 log CFU/cm[superscript]2 reduction of L. monocytogenes was observed after 24 h of storage for turkey tenders for all packaging treatments. After 48 h of storage time turkey tenders showed >1 log CFU/cm [superscript]2 reduction of L. monocytogenes for all packaging treatments except for vacuum packaged where only 0.9 log CFU/cm[superscript]2 reduction was observed. Log reductions at 72 h for all packaging treatments for turkey tenders ranged from 1.5 to 2.2. Processors of kippered beef steak and turkey tenders could use vacuum, nitrogen-flushing, or heat sealed with an oxygen scavenger packaging methods and hold product 24 h prior to shipping to reduce potential L. monocytogenes numbers by ≥1 log. However, processors should be encouraged to hold packaged product a minimum of 72 h to enhance the margin of safety for L. monocytogenes control.
Keywords: snack sticks; Listeria monocytogenes; packaging; kippered beef; turkey; post-lethality; Agriculture, Food Science and Technology (0359)